Kesetaraan Gender dalam Konstruksi Media Sosial - Widodo, Wicha Rizky Sakti Mashito; Nurudin; Widiya Yutanti (Unitri Press, 2021)
Patriarchy results in gender inequality in the social environment. This makes women and men have roles, status and even emotional levels that tend to discriminate. So that researchers are interested in analyzing and criticizing gender inequality in Indonesia through campaigns carried out by the @lawanpatriarki and @lakilakibaru Instagram accounts, where the two accounts have different backgrounds but have one goal. This research uses a qualitative approach with a critical paradigm and an interpretive type. As for the data collection methods used are screenshots of posts on gender equality content and captions on Instagram accounts @lawanpatriarki and @lakilakibaru, notes, journals, books, and articles on the website or the internet. This data collection is used to obtain information regarding the messages that the two accounts convey in the 'Free from Sexual Violence' campaign posts. Then, the data is processed using a discourse analysis text study of Sara Mills. From The research conducted shows that the differences in the background of two accounts have the same goal, namely to voice gender equality which applies to all parties, both men, women and others. Everyone has the right to feel free from sexual violence, especially from the shackles of a patriarchy culture. This is because the patriarchy culture is not only detrimental to women but also men. Keywords: social media construction; gender equality; instagram; rape